A Rapid and Simple Manifold to Study Exchangeable Cations and Cation Exchange Capacity in 24 Soil Samples Simultaneously - Kloster, Nanci Soledad (2020)
The outcomes of this work highlight the development and validation of a rapid and simple manifold for determination of exchangeable cations [calcium (Ca), magnesium (Mg), sodium (Na), and potassium (K)] and cation exchange capacity (CEC) in soil. First, the performance of the manifold was evaluated to determine the best conditions to use: filter assembly, volume and number of aliquots of extracting solution, and the use of vacuum. Second, the analytical performance was study from trueness and precision analysis. For that, soil samples with assigned values, an in house reference material and unknown soil samples, were used, comparing their results with those obtained using the classical extraction method (agitation, centrifugation, and filtration). The performance study showed that a filter system assembled with S&S Nº859 type filter paper, cotton, and plastic piece is better to the other studied options. Four aliquots of 10 mL extracting solution and a few seconds of vacuum between additions is recommended to achieve the best recovery. The extraction procedure proposed using the manifold demonstrated to be accurate, and so can effectively replace the classical method for the extraction of exchangeable cations and CEC in soils. Regarding simplicity, rapidity, and simultaneity, the manifold method could be the method of choice for extraction up to 24 samples. Moreover, the manifold method significantly reduces the laboratory supplies and instrument used in the extraction steps in the classical method, attaining better efficiency and reducing costs associated to this stage of the analysis. Los resultados de este trabajo destacan el desarrollo y validación de una variedad rápida y sencilla para la determinación de cationes intercambiables [calcio (Ca), magnesio (Mg), sodio (Na) y potasio (K)] y la capacidad de intercambio catiónico (CEC) en suelo. En primer lugar, se evaluó el rendimiento del colector para determinar las mejores condiciones de uso: conjunto de filtro, volumen y número de alícuotas de solución de extracción y uso de vacío. En segundo lugar, el rendimiento analítico se estudió a partir del análisis de veracidad y precisión. Para ello se utilizaron muestras de suelo con valores asignados, material de referencia propio y muestras de suelo desconocidas, comparando sus resultados con los obtenidos mediante el método de extracción clásico (agitación, centrifugación y filtración). El estudio de desempeño mostró que un sistema de filtrado ensamblado con papel de filtro tipo S&S Nº859, algodón y pieza plástica es mejor que las otras opciones estudiadas. Se recomiendan cuatro alícuotas de 10 ml de solución de extracción y unos segundos de vacío entre adiciones para lograr la mejor recuperación. El procedimiento de extracción propuesto utilizando el colector demostró ser preciso y, por lo tanto, puede reemplazar eficazmente el método clásico para la extracción de cationes intercambiables y CEC en suelos. En cuanto a simplicidad, rapidez y simultaneidad, el método múltiple podría ser el método de elección para la extracción de hasta 24 muestras. Además, el método múltiple reduce significativamente los suministros de laboratorio e instrumentos utilizados en los pasos de extracción en el método clásico, logrando una mayor eficiencia y reduciendo los costos asociados a esta etapa del análisis.